Pregnancy and Family Planning in Women With Kidney Disease - Joy Eskandar; Anika Lucas; Angelina Dixon; Jessica Kendrick (Kidney International Reports)
Introduction: Females with kidney disease are at increased risk for pregnancy complications. Few studies have examined pregnancy perspectives of people with kidney disease. Our objective was to examine kidney patients’ perspectives on family planning. Methods: We conducted an online survey of female patients with kidney disease from the University of Colorado Hospital between the ages of 18 and 50 years from August to October 2022. The survey asked questions on previous and current pregnancies with kidney disease, family planning, and reproductive health discussions with their nephrologists. Perspectives on how kidney disease influences pregnancies were also explored. Results: A total of 136 participants completed the survey. The majority of participants were White (71.3%) with a mean (SD) age of 37 ± 10 years. The majority of participants self-characterized their kidney disease as moderate (n = 57, 43.5%) with 16 participants (12.2%) receiving dialysis. Fifty-two participants (38.5%) experienced a pregnancy with a diagnosis of kidney disease, which were largely planned (n = 33, 61.1%). The majority of participants were able to conceive within 6 months (64.8%). Nearly half of participants reported that kidney disease influenced their family planning decisions with the majority (n = 91, 66.5%) believing that kidney disease increased their risk for pregnancy complications. More than half of participants never discussed the health risks of a potential pregnancy (54.0%), desire to have children (58.0%), pregnancy prevention (57.0%), and/or optimizing their health prior to pregnancy (68.1%) with their nephrologist. Conclusion: Although kidney disease influenced family planning decisions, few participants had family planning discussions with their nephrologists.